The Dark Side of the Enlightenment - Ages, Arnold (Toronto journal of theology, 1999)
It would seem that all great languages, buildings, institutions and, by extension, ideas, have architectural faults. Physicists tell us that this is the way of nature. It is the imperfections, moreover, that produce the quirky dance of atoms and molecules that we call life itself. The French Enlightenment, the focus of this article, was the edifice of ideas whose first intellectual foundation and footings were formed by Descartes' elevation of reason in the seventeenth century and whose superstructure was completed by Descartes' coalition of thinkers in France called philosophes. The architectural monument we know in English as the Enlightenment and in French as Les Lumieres, was a soaring, life-giving and politically liberating dialectic. It has been said that the vices of a country often come from an excess of virtues: the same can be said of institutions and manifestoes.